Cultural Planning in the Eastern Pori Suburbs: Applicability of the Approach? - Häyrynen, Maunu (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
This paper describes an attempt to apply cultural planning in a group of high-rise suburbs with an aging population in the mid-size city of Pori, on the West Coast of Finland. First, the background of the project and the motive for adopting a cultural planning approach is explained. A preceding pilot study on cultural planning in Finland is described, providing background information about the recent spread of the approach into the country and the current state of cultural planning processes. Second, the starting points and conceptual framework of the cultural planning project are briefly discussed in the light of research literature. After that, the objectives of the cultural mapping phase and the baseline studies linked with it are elaborated. Cultural resources of the Eastern Pori suburbs, as identified in the mapping, are analyzed. Prescriptions for cultural development follow, based on collaborative planning and focusing on public spaces and community art in the Eastern suburbs. Finally, the further applicability of cultural planning in the Finnish context is assessed, judging from the Pori experience.